Aftercare for Survivors of Human Trafficking: A Case Study on Optimal Approach to Recovery and Integration - Abayle, Cherrelyn L.; Candilas, Kurt (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Human trafficking is a modern-day slavery that mostly disproportionate women in the society. This study aimed to fill the knowledge gaps regarding the aftercare experiences of human trafficking survivors as they navigated their recovery and reintegration into society, with a specific focus on the Philippines. The research investigated the effectiveness of aftercare interventions provided by agency, highlighting the importance of comprehensive and customized support systems. It drew on Empowerment Theory and Ecological Systems Theory to inform its analysis. The study utilized a qualitative intrinsic case study design, employing purposeful sampling to gather insights from social worker, psychologist, house parents, survivors and other professional involved in aftercare. Collecting data using typically involved conducting in-depth interviews, engaging with key informants, and facilitating focus group discussions. Emerging themes were analyzed using Braun and Clarke’s method of thematic analysis. The study uncovered two main themes: "Grappling with Adversities" and "Socio-emotional Transformation." It provided insight into the challenges and situations experienced by survivors, as well as the influence of support systems, healing processes, and personal development initiatives on their recovery. The research highlighted the significance of education, development of independent living skills, and provision of emotional support in empowering survivors. Suggested measures involved the establishment of thorough post-treatment support initiatives, public initiatives to raise awareness within the community, and ongoing professional training for workers. This study added to our knowledge of survivor empowerment within the realm of human trafficking and emphasized the importance of continued research and evaluation of aftercare programs.